临床预测模型开发与验证的统计分析思路及图表概述 - 杜柯瑾; 谷鸿秋 (Zhongguo cuzhong zazhi, 2024)
统计图表的呈现对临床预测模型研究质量的提升非常重要。本文将临床预测模型的统计图表归纳为描述基本信息、报告模型信息、评价模型表现以及展现应用模型4个方面，并配以统计图表模板进行简要概述。 Abstract: The presentation of statistical charts plays a crucial role in improving the quality of clinical prediction model research. This paper categorized statistical charts in clinical prediction models into four aspects: describing basic information, reporting model information, evaluating model performance, and demonstrating model application, accompanied by a brief overview of statistical chart templates.